SEI film-forming additive for inhibiting hydrogen evolution of aqueous battery negative electrode and application of SEI film-forming additive
By using CFx as an SEI film-forming additive in the anode of aqueous batteries, a metal fluoride SEI layer is generated, which solves the problem of hydrogen evolution in aqueous batteries and achieves extended cycle life and low-cost and efficient SEI construction.
Patent Information
- Application Number
- CN202311224938.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-01-21
AI Technical Summary
The hydrogen evolution problem of water-based batteries during circulation is serious, affecting the efficiency and cycle life of Coulomb. The existing technology methods for suppressing hydrogen evolution are costly, low output, and cumbersome, so they cannot be suitable for large-scale applications.
CFX is used as a SEI film additive with a water-based battery negative electrode. The chemical formula is CFX and X is 0.6-1.2. It is restored to form metal fluoride and forms the SEI layer to suppress hydrogen.
Through a simple doping method, the SEI layer is constructed cost-effectively, suppresses hydrogen evolution side reactions, and extends the cycle life of aqueous batteries. The reaction only occurs during the first week of charging and does not affect subsequent charge and discharge curves.
Smart Images

Figure CN119340394A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aqueous battery, and in particular to an aqueous battery negative electrode hydrogen evolution inhibition SEI film-forming additive and application thereof. Background Art
[0002] Aqueous batteries are safe, environmentally friendly, and low-cost. Compared with organic batteries, they have advantages such as simple preparation process, low environmental requirements, and most importantly, intrinsic safety. However, the problem of hydrogen evolution during the cycle of aqueous batteries has always been a major factor restricting its development. The main reason is that the electrochemical stability window of the electrolyte with water as the solvent is narrow, and the potential of water reduction hydrogen evolution is high, which leads to the inevitable occurrence of hydrogen evolution side reactions during the cycle, affecting the coulomb efficiency and thus reducing the cycle life of the battery. Therefore, finding a way to inhibit hydrogen evolution at the negative electrode is crucial for the development of aqueous batteries.
[0003] The construction of the negative electrode solid electrolyte interphase (SEI) can reduce the contact between water molecules in the electrolyte and the electrode active substances, while increasing the polarization of the negative electrode side reaction and thus weakening the hydrogen evolution effect. Artificial SEI technology is a technology that artificially generates and controls the solid electrolyte interface layer in lithium-ion batteries or other types of batteries. At present, artificial SEI technologies, such as atomic layer deposition, chemical vapor deposition, and active material coating, all have problems such as high cost, low yield, and cumbersome steps, and are not suitable for large-scale applications.
[0004] Chinese invention patent CN 106395741 A (publication date February 15, 2017) discloses a method for preparing negative electrode materials from graphite fluoride and carbon nanotubes. Graphite fluoride is used as the main material as an active substance, and carbon nanotubes are used as a coating layer to obtain a composite negative electrode material. This invention scheme is applied to the field of organic lithium-ion batteries. For aqueous batteries, graphite fluoride negative electrode materials cannot be used as a suitable recycling material because the electrochemical stability window of water is very narrow and the graphite negative electrode reaction potential formed after the graphite fluoride reaction is very low, so it cannot be used in aqueous batteries. The technical scheme of Chinese invention patent CN111628168A is similar to it, disclosing a method for preparing graphite fluoride and coating it with hard carbon to further improve its performance. It is also used as a negative electrode active material for organic lithium-ion batteries and cannot be used in aqueous batteries.
[0005] Chinese invention patent CN 103700858 A discloses a method for preparing a sodium-carbon fluoride primary battery. The patent uses carbon fluoride as the main material of the positive electrode material of the sodium ion battery, and uses a sodium salt electrolyte containing an organic solution as a solvent as the electrolyte. However, for aqueous batteries, the graphite negative electrode reaction potential formed after the graphite fluoride reaction is very low, and it cannot be used as an active material for the negative electrode material, let alone as an active material for the positive electrode material. Chinese invention patent CN 114628670 A is similar to this. Carbon fluoride is nitrogen-doped and carbon-coated, and then used as a positive electrode material in lithium / carbon fluoride organic lithium ion batteries. It is also used as a positive electrode active material for organic lithium ion batteries and is not suitable for use in aqueous batteries.
[0006] Chinese invention patent CN 111244406 A discloses a method for modifying titanium dioxide materials with fluorinated graphene. The patent uniformly mixes fluorinated graphene and titanium-based materials in liquid phase and then calcines at high temperature to form a titanium dioxide negative electrode material modified by fluorinated graphene. Since CF-Ti bonds are formed on the surface of titanium dioxide, and titanium dioxide and fluorinated graphene are compounded at the atomic scale, the pole sheet resistance is greatly reduced, thereby improving the material rate performance. The method for modifying titanium dioxide in this patent is complicated, requiring liquid phase mixing and high-temperature calcination, and its target is only for titanium dioxide negative electrode materials, which has limitations. Because it clearly points out that the principle of action is to form CF-Ti bonds on the surface of titanium dioxide, it can be seen that titanium dioxide is specific to this method, indicating that the treatment method of fluorinated graphene is not suitable for other lithium-ion battery negative electrode materials. The patent uses fluorinated graphene to modify titanium dioxide materials, specifically to improve the conductivity of the material and the rate performance of the negative electrode, and it cannot achieve the effect of inhibiting hydrogen evolution.
[0007] Chinese invention patent CN 104993145 A discloses a method of using fluorinated graphene as a conductive agent for positive electrode materials of lithium-ion batteries. The patent proposes adding fluorinated graphene to lithium-ion batteries as a conductive additive to improve the conductivity of the positive electrode and improve the wettability of the electrode with the electrolyte. The patent improves the kinetic performance of the electrode by improving the conductivity of the electrode, thereby improving the rate performance. In this technical solution, fluorinated graphene is used as a conductive additive for the positive electrode to improve the process of conducting electrons in the electrode material; because the positive electrode potential of the lithium-ion battery is relatively high, an oxidation reaction occurs during the charging process, and therefore the fluorinated graphene in the positive electrode material cannot be reduced at the positive electrode, and a solid electrolyte interface cannot be formed. Summary of the invention
[0008] The purpose of the present invention is to provide an aqueous battery negative electrode SEI film-forming additive for inhibiting hydrogen evolution and application thereof.
[0009] To this end, in the first aspect, the embodiment of the present invention provides a water-based battery negative electrode to inhibit hydrogen evolution solid electrolyte interface SEI film-forming additive, the chemical formula of the SEI film-forming additive is CF x , x is 0.6-1.2;
[0010] The CF x Specifically including: a mixture of one or more of fluorinated graphite, fluorinated carbon, fluorinated graphene or fluorinated carbon nanotubes;
[0011] During the first week of charging of the aqueous battery, a reduction reaction occurs at the negative electrode of the aqueous battery, and the SEI film-forming additive CF x The metal fluoride is reduced to form a SEI layer on the negative electrode of the aqueous battery.
[0012] Preferably, the aqueous battery is an aqueous lithium ion battery or an aqueous sodium ion battery;
[0013] The aqueous battery negative electrode undergoes a reduction reaction, and the SEI film-forming additive CF x The reaction process of reduction to form metal fluoride is:
[0014] CF x (s)+xZ + (aq)+xe - →xZF(s)+C(s); where Z is Li or Na;
[0015] e - Electrons are transmitted to the negative electrode through an external circuit to participate in the electrochemical reaction during the charging process of the aqueous battery.
[0016] Preferably, the SEI film-forming additive CF x The lateral dimension, i.e. the flake diameter, is less than 20 microns.
[0017] In a second aspect, an embodiment of the present invention provides an aqueous battery negative electrode plate, comprising the aqueous battery negative electrode SEI film-forming additive for inhibiting hydrogen evolution as described in the first aspect above.
[0018] Preferably, the mass proportion of the aqueous battery negative electrode hydrogen evolution inhibiting SEI film-forming additive in the aqueous battery negative electrode plate is 0.5%-8%.
[0019] In a third aspect, an embodiment of the present invention provides a method for forming an SEI layer on an aqueous battery negative electrode sheet by using the aqueous battery negative electrode SEI film-forming additive for inhibiting hydrogen evolution as described in the first aspect, the method comprising:
[0020] Preparation of CF containing SEI film-forming additives x The negative electrode sheet; x is 0.6-1.2;
[0021] Assembling an aqueous battery using the negative electrode sheet;
[0022] The aqueous battery is charged. During the first week of charging of the aqueous battery, a reduction reaction occurs at the negative electrode of the aqueous battery, and the SEI film-forming additive CF x The metal fluoride is reduced to form a SEI layer on the negative electrode of the aqueous battery;
[0023] Wherein, the reaction process of the reduction is:
[0024] CF x (s)+xZ + (aq)+xe - →xZF(s)+C(s); where Z is Li or Na;
[0025] e - Electrons are transmitted to the negative electrode through an external circuit to participate in the electrochemical reaction during the charging process of the aqueous battery.
[0026] Preferably, the preparation contains SEI film-forming additive CF x The negative electrode sheet specifically includes:
[0027] The negative electrode active material and SEI film-forming additive CF x , the conductive additive is uniformly mixed and ground, and then a binder is added, and the mixture is stirred and mixed to obtain a slurry;
[0028] The negative electrode sheet is obtained by preparing the slurry by a coating method or a dry method.
[0029] Further preferably, the negative electrode active material comprises: an aqueous lithium ion battery negative electrode active material or an aqueous sodium ion battery negative electrode active material;
[0030] The conductive additive includes: a mixture of one or more of carbon black, graphene, acetylene black, Ketjen black, Super P, and carbon nanotubes;
[0031] The binder comprises: a mixture of one or more of polyvinylidene fluoride PVDF, polytetrafluoroethylene PTFE, acrylamide-acrylate copolymer, and sodium alginate.
[0032] In a fourth aspect, an embodiment of the present invention provides an aqueous lithium-ion battery, comprising the aqueous battery negative electrode plate described in the second aspect above.
[0033] In a fifth aspect, an embodiment of the present invention provides an aqueous sodium ion battery, comprising the aqueous battery negative electrode plate described in the second aspect above.
[0034] The aqueous battery negative electrode SEI film-forming additive for inhibiting hydrogen evolution provided by the embodiment of the present invention has the advantages of light weight, good conductivity, stable chemical properties, simple and safe ingredients, etc. It can be applied to the negative electrode by simple doping, and the electrochemical reaction of the SEI film-forming additive is realized through the natural first-week charging and discharging process of the battery, thereby forming a uniform SEI layer on the surface of the negative electrode active material; the reaction of the additive only occurs in the first-week charging process, and then will not affect the subsequent charging and discharging curves of the battery, and the construction of the aqueous battery SEI can be realized at low cost and high efficiency, thereby inhibiting the contact between water molecules in the aqueous electrolyte and the electrode active material, and improving the polarization of the side reaction, thereby inhibiting hydrogen evolution and extending the cycle life of the aqueous battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The SEI additive CF provided in the embodiment of the present invention x Schematic diagram of the reaction;
[0036] Figure 2 CF provided by the embodiment of the present invention x XRD pattern of the negative electrode after the first week of charge and discharge;
[0037] Figure 3 The CF-doped and CF-free samples provided in Example 1 and Comparative Example 1 of the present invention are x XPS spectrum of the negative electrode after the first week of charge and discharge;
[0038] Figure 4 The CF-doped x TEM spectrum of the negative electrode after the first week of charge and discharge;
[0039] Figure 5 The CF-doped x The hydrogen production rate-electrochemical curve of the negative electrode during the charge and discharge process;
[0040] Figure 6 The comparative example 1 of the present invention does not contain CF x The hydrogen production rate-electrochemical curve of the negative electrode during the charge and discharge process;
[0041] Figure 7 The lithium manganese oxide positive electrode-CF in the three-electrode device of the battery provided in Example 1 and Comparative Example 1 of the present invention x The first week charge and discharge curve of TiO2-doped negative electrode aqueous battery;
[0042] Figure 8 The lithium manganate positive electrode provided in Example 1 of the present invention - CF x Cycle-specific capacity curve of aqueous battery with doped titanium dioxide negative electrode;
[0043] Fig. 9 A cycle-specific capacity curve of a lithium manganate positive electrode-titanium dioxide negative electrode aqueous lithium ion battery provided in Comparative Example 1 of the present invention;
[0044] Fig.10 This is a cycle-specific capacity curve of a lithium manganese oxide positive electrode-titanium dioxide negative electrode aqueous battery provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0045] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.
[0046] The embodiment of the present invention provides a water-based battery negative electrode solid electrolyte interface SEI film-forming additive for inhibiting hydrogen evolution, the chemical formula of the SEI film-forming additive is CF x , x is 0.6-1.2;
[0047] CF x Specifically including: a mixture of one or more of fluorinated graphite, fluorinated carbon, fluorinated graphene or fluorinated carbon nanotubes;
[0048] During the first week of charging of the aqueous battery, a reduction reaction occurs at the negative electrode of the aqueous battery, and the SEI film-forming additive CF x It is reduced to form metal fluoride, forming a SEI layer on the negative electrode of the aqueous battery.
[0049] The aqueous battery of the present invention specifically includes an aqueous lithium ion battery or an aqueous sodium ion battery;
[0050] SEI film forming additive CF x The reaction process of reduction to form metal fluoride is:
[0051] CF x (s)+xZ + (aq)+xe - →xZF(s)+C(s) Formula (1);
[0052] Wherein, Z is Li or Na;
[0053] In the above reaction equation, e - Electrons are transferred to the negative electrode through an external circuit to participate in the electrochemical reaction during the charging process of the aqueous battery. + ) comes from the electrolyte. (s) means the substance is in solid state, and (aq) means the substance is in solution.
[0054] The ZF generated in this reaction is specifically lithium fluoride (LiF) or sodium fluoride (NaF), which will become a part of the SEI layer, and the generated carbon material (C) may also remain in the SEI layer and together constitute a component of the SEI layer.
[0055] The aqueous battery negative electrode hydrogen evolution inhibition SEI film-forming additive of the present invention is used in the aqueous battery negative electrode plate. The negative electrode materials that together constitute the negative electrode plate also include: negative electrode active material, conductive additive and binder.
[0056] The negative electrode active material includes: aqueous lithium ion battery negative electrode active material or aqueous sodium ion battery negative electrode active material; wherein the aqueous lithium ion battery negative electrode active material includes but is not limited to TiO2, Mo6S8, Li4Ti5O 12 , LiV3O8, LiTi2(PO4)3, TiP2O7, etc.; the negative electrode active materials of aqueous sodium ion batteries include but are not limited to NaTi2(PO4)3, V2O5, VO2, NaV6O 15 wait.
[0057] Conductive additives include: a mixture of one or more of carbon black, graphene, acetylene black, Ketjen black, Super P, and carbon nanotubes;
[0058] The binder includes: a mixture of one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), acrylamide-acrylate copolymer, and sodium alginate.
[0059] The film-forming additive CF proposed by the present invention x The transverse dimension (i.e., the sheet diameter) is less than 20 microns. Preferably, less than 10 microns.
[0060] Due to the different types of negative electrode active materials, the actual added SEI film-forming additive CF x The optimal ratio of conductive additives and binders will also change accordingly. Here are several preferred solutions, which are only for illustration and are not intended to limit the scope of the technical solutions that can be implemented in the present invention. For negative electrode active materials with poor conductivity, a ratio of negative electrode active material: CF x The negative electrode sheet is prepared by mixing the conductive additive and the binder in a ratio of 75:5:10:10. For the negative electrode active material with slightly better conductivity, the ratio of negative electrode active material: CF x : Conductive additive: binder is 80:5:5:10. For applications that require high energy density, it can be adjusted to negative electrode active material: CF x : Conductive additive: binder is 90:2:3:5. Because different negative electrode materials have different conductivity and potential in aqueous batteries, the intensity of hydrogen evolution side reaction on the surface is also different, so SEI film-forming additive CF x The amount of addition is changed accordingly. In the present invention, the SEI film-forming additive CF x The mass proportion of the negative electrode plate of the aqueous battery is 0.5%-8%, preferably 1%-5%.
[0061] Figure 1 The SEI additive CF provided in the embodiment of the present invention x The reaction principle diagram is as follows: Figure 1 As shown, before the first cycle, CF x And carbon black (conductive additive) are evenly dispersed around the negative electrode active material. Due to the loose structure of carbon black, there are many pores inside the negative electrode material and it is filled with electrolyte.
[0062] During the first week of charging, the positive electrode releases metal cations, moves to the negative electrode interface, desolvates, enters the negative electrode material, and reacts with CF x Reactions occur to generate metal fluorides that are insoluble in water. As the charging process proceeds, CF x Gradually reduced, the SEI layer gradually forms on the surface of the negative electrode active material, inhibiting the hydrogen evolution reaction on the surface of the negative electrode active material. x After sufficient reduction, a SEI layer mainly composed of metal fluorides is formed on the surface of the negative electrode active material.
[0063] Because CF x The reduction potential is about 2.5V to lithium, which is higher than the lithium insertion potential of the negative electrode active material of the general aqueous battery. This leads to the metal cations in the positive electrode active material being released during the first week of charging, and the reduction reaction of the negative electrode is carried out by the higher potential CF x First, so that in CF x After the metal fluoride SEI layer is formed by reduction, the metal cations of the positive electrode active material continue to be released, and the negative electrode reduction reaction is the embedding of metal ions into the negative electrode active material, specifically lithium or sodium. That is, during the first week of charging, the negative electrode reaction has two processes. First, CF x The process of reducing to form SEI, and then the normal lithium or sodium insertion process. In the subsequent cycles, CF x Since it has been consumed in the first week, it will no longer participate in the electrode reaction.
[0064] Preferably, before the aqueous battery is put into normal circulation, a formation process is first performed to complete the CF x reduction, and the formation of a SEI layer containing LiF or NaF.
[0065] In order to verify the feasibility of this method, we designed the following experimental process:
[0066] In aqueous lithium-ion batteries, the mass ratio of graphite fluoride: carbon black: polyvinylidene fluoride (PVDF) = 8:1:1 is used as the negative electrode active material, in which PVDF exists in the form of being dissolved in NMP solution. After grinding the active material and conductive additives thoroughly, add PVDF, and evenly mix them at high speed in the mixer, and then evenly apply the slurry on the aluminum foil. After it is completely dried, use the slicing mechanism to obtain the negative electrode. The positive electrode active material uses lithium manganate LiMn2O4. The positive electrode active material LiMn2O4, the conductive additive carbon black, and the polyvinylidene fluoride (PVDF) binder are weighed according to the mass ratio of 8:1:1, in which PVDF exists in the form of being dissolved in N-methylpyrrolidone (NMP) solution. After grinding the active material and conductive additives thoroughly, add PVDF, and evenly mix them at high speed in the mixer, and then evenly apply the slurry on the aluminum foil. After it is completely dried, use the slicing mechanism to obtain the positive electrode. The electrolytes used were 20 mol / Kg LiCl and 10 mol / Kg LiTFSI, with a positive electrode and a negative electrode mass ratio of 2:1. The aqueous battery device was assembled with an aluminum-plastic film as the shell and a glass fiber as the diaphragm. Constant current charge and discharge tests were performed with a rate of 1C, a charge cutoff voltage of 2.5V, and a discharge cutoff voltage of 0.9V.
[0067] After the battery completes the first week of charge and discharge, the negative electrode is taken out, washed with alcohol for several times, and then characterized by X-ray diffraction (XRD). x XRD pattern of the negative electrode after the first week of charge and discharge; Figure 2 At the bottom is the standard PDF card of LiF. It can be seen that in 20m LiCl electrolyte, three strong peaks of LiF are clearly seen in the XRD spectrum, proving that CF x In this system, LiF can be decomposed. Since LiCl electrolyte does not contain F element, the electrolyte will not react to form LiF at the negative electrode, so it will not affect the experimental results. Therefore, LiF can only be CF. 0.9 In the 10 m LiTFSI electrolyte system, three strong peaks of LiF were also observed, proving that CF in formula (1) x The reaction mechanism also proves that this patent will CF x Feasibility as a negative electrode SEI additive.
[0068] The embodiment of the present invention is directed to the proposed SEI film-forming additive CF for inhibiting hydrogen evolution at the negative electrode of an aqueous battery. x , provides CF x The specific usage and principle of CF x The formation of SEI containing LiF or NaF can inhibit the hydrogen evolution side reaction and prolong the life of aqueous batteries. xThere are various types, such as fluorinated graphite, fluorinated graphene, fluorinated carbon nanotubes, etc. x It has the characteristics of being stable in water, and when it is charged, CF x When reduced at the negative electrode, the product LiF or NaF acts as the SEI layer to inhibit the contact between water molecules in the solution and the electrode active material, and to increase the polarization of the side reaction, thereby inhibiting hydrogen evolution and extending the cycle life of the aqueous battery device. Compared with the traditional methods of treating active materials by atomic layer deposition, chemical vapor deposition, coating, etc., the present invention utilizes CF in the negative electrode plate to x The simple doping of the additives realizes the electrochemical reaction of the additives through the natural charge and discharge process of the battery, thereby forming a uniform LiF or NaF passivation layer on the surface of the active material. The additive reaction only occurs during the first week of charging, and after completion it will no longer affect the subsequent charge and discharge curves of the battery. It can form the SEI of the aqueous battery at low cost and high efficiency and extend the life of the aqueous battery.
[0069] Aqueous battery negative electrode SEI additive CF provided by the embodiment of the present invention x , has the advantages of light weight, large-scale preparation, good conductivity, etc. Its chemical properties are stable, its ingredients are simple and safe, and it can be used on a large scale in aqueous batteries.
[0070] Aqueous battery negative electrode SEI additive CF provided by the embodiment of the present invention x The SEI components produced by the reaction are mainly LiF or NaF. LiF and NaF are both stable in nature and are common SEI components of aqueous batteries. They do not conflict with other components of the battery and can effectively protect the negative electrode of the aqueous battery for a long time.
[0071] Aqueous battery negative electrode SEI additive CF provided by the embodiment of the present invention x The main steps of using the method are to treat the negative electrode active material and CF under normal conditions at room temperature. x , the conductive additive is evenly mixed and stirred in a mortar, and then a binder is added to prepare the battery electrode by coating or dry method. This method is simple and easy, does not require high temperature reaction, and does not require special equipment, and can achieve efficient production and preparation of battery negative electrodes.
[0072] Aqueous battery negative electrode SEI additive CF provided by the embodiment of the present invention x The electrochemical reaction conditions are simple, and the reduction can be achieved as long as the potential reaches about 2.5V to lithium. The reaction potential of conventional negative electrode active materials is basically lower than this value, so the formation of the SEI layer of the present invention can be achieved very simply.
[0073] In order to more clearly illustrate the purpose and advantages of the present invention, the present invention is further described below in conjunction with the embodiments. In addition, the embodiments described in the present invention are only partial embodiments. Based on the embodiments described in the present invention, all other embodiments obtained by those skilled in the art without creative work are within the protection scope of the present invention. In addition, it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.
[0074] Example 1
[0075] This example provides the test and application of SEI film-forming additives for aqueous battery negative electrode to inhibit hydrogen evolution, and is used to further verify the CF x reaction mechanism.
[0076] The aqueous lithium-ion battery is assembled with graphite fluoride negative electrode and lithium manganese oxide positive electrode. In this example, the chemical formula of graphite fluoride is CF 0.9 , the fluorine-carbon ratio is 0.9, and the sheet diameter is less than 10 microns.
[0077] Preparation of positive electrode: The positive electrode active material is lithium manganate LiMn2O4. The positive electrode active material LiMn2O4, the conductive additive carbon black, and the polyvinylidene fluoride (PVDF) binder are weighed in a mass ratio of 8:1:1, wherein PVDF exists in the form of being dissolved in N-methylpyrrolidone (NMP) solution. After the active material and the conductive additive are fully ground, PVDF is added, and after high-speed uniform mixing in a mixer, the slurry is evenly coated on aluminum foil. After being completely dried, the positive electrode is obtained using a slicing mechanism.
[0078] Preparation of negative electrode: Titanium dioxide TiO2 is selected as the negative electrode material. The negative electrode active material TiO2, SEI film-forming additive graphite fluoride, conductive additive carbon black, and PVDF binder are weighed according to the mass ratio of 75:5:10:10, where PVDF exists in the form of dissolving in NMP solution. After the active material and conductive additive are fully ground, PVDF is added. After high-speed uniform mixing in the mixer, the slurry is evenly coated on the aluminum foil. After it is completely dried, the slicing mechanism is used to obtain the negative electrode. Among them, the mass ratio of positive electrode to negative electrode is 2:1.
[0079] Electrolyte system: The electrolyte is a 10 mol / Kg (mass molar concentration) lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) solution, and the solvent is water.
[0080] The aqueous battery device of this embodiment is assembled using an aluminum-plastic film as the shell and a glass fiber as the diaphragm.
[0081] Comparative Example 1 was prepared according to the method of Example 1, except that no graphite fluoride was added. In terms of mass ratio, titanium dioxide: conductive additive conductive carbon black: binder PVDF = 8:1:1.
[0082] The constant current charge and discharge test was adopted, the rate was 1C, the charge cut-off voltage was 2.5V, and the discharge cut-off voltage was 0.9V.
[0083] Figure 3 The CF-doped and CF-free samples provided in Example 1 and Comparative Example 1 of the present invention are x XPS spectrum of the negative electrode after the first week of charge and discharge.
[0084] Similar to the above treatment method, after the first week of charge and discharge of the battery is completed, the negative electrode plate is removed for XPS characterization, and the F1s spectral peak is analyzed. It can be seen that after the cycle of the comparative battery, that is, the negative electrode plate without graphite fluoride, only the CF peak in PVDF can be seen, and no Li-F peak can be seen, indicating that the amount of LiF is very small, so the SEI content of the negative electrode is very low. This is also the reason why the battery of comparative example 1 has serious hydrogen evolution at the negative electrode interface during the cycle, that is, there is no SEI to protect the negative electrode interface. In contrast, the battery of Example 1, that is, the negative electrode plate doped with graphite fluoride, can clearly see the Li-F peak near 685.10 after the first week of charge and discharge, indicating that CF x More LiF is produced, and LiF is an important component of inorganic SEI, which has an inhibitory effect on the hydrogen evolution reaction at the negative electrode interface. This result further verifies that CF x reaction mechanism.
[0085] Figure 4 The CF-doped x TEM spectrum of the negative electrode after the first week of charge and discharge. The sample used for TEM test and the above XPS test sample are two different samples cut from the same negative electrode sheet.
[0086] After analyzing the lattice fringes of the TEM results, the (011) fringes of TiO2 are found in the lower right corner, indicating that the lower right corner is a TiO2 particle. The (111) and (222) fringes of LiF are found on its left side. It can be clearly seen that there is a LiF coating layer, which will inhibit the adsorption of water molecules on the TiO2 particles. The experimental results prove that the fluorinated graphite CF x Feasibility of using it as a SEI additive to inhibit hydrogen evolution.
[0087] The hydrogen production rate inside the battery was tested by in-situ differential electrochemical mass spectrometry (DEMS) during the charge and discharge process of the aqueous lithium-ion battery of Example 1, which had a lithium manganese oxide positive electrode and a titanium dioxide negative electrode doped with graphite fluoride, and the aqueous lithium-ion battery of Comparative Example 1, which had a lithium manganese oxide positive electrode and a titanium dioxide negative electrode. Figure 5 The CF-doped x The hydrogen production rate-electrochemical curve of the negative electrode during the charge and discharge process; Figure 6 The comparative example 1 of the present invention does not contain CF x The hydrogen production rate-electrochemical curve of the negative electrode during the charging and discharging process.
[0088] The battery charge and discharge rate is 1C. In the figure, the upper vertical axis is the battery voltage (V), the horizontal axis is time (min), and the lower vertical axis is the hydrogen generation rate inside the battery (nmol / min), and the horizontal axis is time (min). Figure 5 During the first cycle of charge and discharge, CF x The decomposed LiF immediately begins to inhibit hydrogen evolution, and the rate of hydrogen generation is much lower than Figure 6 The battery without graphite fluoride was used. In the following weeks of cycling, the hydrogen production of the battery was still suppressed, the hydrogen production rate was very low, and it continued to decline. Figure 6 As shown, it can be clearly seen that the battery produces hydrogen at a higher rate and maintains a very high level in subsequent cycles, resulting in a continuous attenuation of the battery capacity.
[0089] The lithium manganese oxide positive electrode-titanium dioxide negative electrode aqueous lithium ion battery of Example 1 and the lithium manganese oxide positive electrode-titanium dioxide negative electrode aqueous lithium ion battery of Comparative Example 1 were tested in a three-electrode system, wherein the reference electrode was a silver / silver chloride electrode, the working electrode was a titanium dioxide negative electrode, and the counter electrode was a lithium manganese oxide positive electrode. The device was used to observe the change in the negative electrode potential during the charge and discharge process. Figure 7 The lithium manganese oxide positive electrode-CF in the three-electrode device of the battery provided in Example 1 and Comparative Example 1 of the present invention x The first week charge and discharge curve of the aqueous battery with TiO2-doped negative electrode. In the figure, the vertical axis below is the lithium potential (V) of the negative electrode, the horizontal axis is the specific capacity (mAh / g), and the charge and discharge rate is 1C. It can be seen that the negative electrode doped with graphite fluoride begins to reduce at 2.35V to lithium during the charging process, which is presented as a slope in the figure. The reduction process is completed at about 2.05V to lithium, followed by a platform of about 2.0V corresponding to the voltage platform of TiO2 embedded in lithium ions, and finally a hydrogen evolution platform appears at 1.9V to lithium. Figure 7 This indicates that graphite fluoride can be fully reduced before TiO2 works, forming a SEI layer on the surface of the negative electrode active material, protecting the negative electrode interface, and inhibiting the hydrogen evolution reaction in the subsequent TiO2 lithium insertion process.
[0090] Example 2
[0091] This example provides the test and application of SEI film-forming additives for aqueous battery negative electrode to inhibit hydrogen evolution, and is used to further verify the CFx reaction mechanism.
[0092] The aqueous lithium-ion battery is assembled with graphite fluoride negative electrode and lithium manganese oxide positive electrode. In this example, the chemical formula of graphite fluoride is CF 0.9 , the fluorine-carbon ratio is 0.9, and the sheet diameter is less than 10 microns.
[0093] Preparation of positive electrode: The positive electrode active material is lithium manganate LiMn2O4. The positive electrode active material LiMn2O4, the conductive additive carbon black, and the polyvinylidene fluoride (PVDF) binder are weighed in a mass ratio of 8:1:1, wherein PVDF exists in the form of being dissolved in N-methylpyrrolidone (NMP) solution. After the active material and the conductive additive are fully ground, PVDF is added, and after high-speed uniform mixing in a mixer, the slurry is evenly coated on aluminum foil. After being completely dried, the positive electrode is obtained using a slicing mechanism.
[0094] Preparation of negative electrode: Titanium dioxide TiO2 is selected as the negative electrode material. The negative electrode active material TiO2, SEI film-forming additive graphite fluoride, conductive additive carbon black, and PVDF binder are weighed according to the mass ratio of 75:5:10:10, where PVDF exists in the form of dissolving in NMP solution. After the active material and conductive additive are fully ground, PVDF is added. After high-speed uniform mixing in the mixer, the slurry is evenly coated on the aluminum foil. After it is completely dried, the slicing mechanism is used to obtain the negative electrode. Among them, the mass ratio of positive electrode to negative electrode is 2:1.
[0095] Electrolyte system: The electrolyte is a 20 mol / Kg (mass molar concentration) lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) solution, and the solvent is water.
[0096] The aqueous battery device of this embodiment is assembled using an aluminum-plastic film as the shell and a glass fiber as the diaphragm.
[0097] The constant current charge and discharge test was adopted, the rate was 1C, the charge cut-off voltage was 2.5V, and the discharge cut-off voltage was 0.9V.
[0098] Comparative Example 2 was prepared according to the method of Example 2, except that no graphite fluoride was added. In terms of mass ratio, titanium dioxide: conductive additive conductive carbon black: binder PVDF = 8:1:1.
[0099] Long cycle tests were performed on the aqueous lithium-ion batteries prepared in Example 2 and Comparative Example 2 on the Land system.
[0100] Figure 8 The lithium manganate positive electrode provided in Example 2 of the present invention -CF xCycle-specific capacity curve of aqueous battery with doped TiO2 negative electrode. The vertical axis is battery voltage, and the horizontal axis is specific capacity. The curves in the figure are the charge and discharge curves of the 1st week, 2nd week, 10th week, 100th week, 500th week, and 1000th week, respectively. It can be seen that graphite fluoride is reduced during the first week of charging, and the voltage is about 1.8V to 2.2V, contributing about 50mAh / g of specific capacity. Then, starting from the second week, there is no "slope" of graphite fluoride reduction in the charge and discharge curves in the figure, indicating that graphite fluoride no longer participates in the reaction process of the electrode.
[0101] Fig. 9 A cycle-specific capacity curve of a lithium manganate positive electrode-titanium dioxide negative electrode aqueous lithium ion battery provided in Comparative Example 2 of the present invention; Fig.10 The cycle-specific capacity curve of the lithium manganese oxide positive electrode-TiO2 negative electrode aqueous battery provided in Example 2 of the present invention. The vertical axis on the left of the figure represents the specific capacity (mAh / g), the vertical axis on the right represents the coulomb efficiency (%), and the horizontal axis is the number of cycles. It can be seen that the battery of Example 2 can maintain 72.2% of its capacity after 1000 cycles of charge and discharge at a rate of 1C, and the average coulomb efficiency is as high as 99.77%. Fig. 9 It can be clearly seen that the battery capacity of Comparative Example 2 decays rapidly, and after 1000 cycles it can only maintain half of its initial capacity. Fig. 9 The experimental results of Comparative Example 2 show that the capacity decay of Example 2 is significantly slower, proving that the capacity decay caused by the hydrogen evolution side reaction at the negative electrode interface is significantly suppressed. In terms of coulombic efficiency, the 99.77% of Example 2 is also significantly higher than 99.33%, proving that CF x Effectiveness as a negative electrode SEI additive.
[0102] Example 3
[0103] This embodiment provides a LiMn2O4-Mo6S8 aqueous battery device and a method for extending cycle life. The preparation process of the LiMn2O4-Mo6S8 aqueous battery device specifically includes:
[0104] Preparation of positive electrode: The positive electrode active material is lithium manganese oxide LiMn2O4. Weigh the positive electrode active material LiMn2O4, the conductive additive acetylene black, and the sodium alginate binder according to the mass ratio of 8:1:1. After the active material and the conductive additive are fully ground, add the sodium alginate, mix them evenly at high speed in the mixer, and then evenly apply the slurry on the aluminum foil. After it is completely dried, use the slicing mechanism to obtain the positive electrode.
[0105] Preparation of negative electrode: Mo6S8 is selected as the negative electrode material. Mo6S8, the negative electrode active material, the SEI film-forming additive carbon fluoride, the conductive additive acetylene black, and the sodium alginate binder are weighed according to the mass ratio of 90:0.5:9.5:10. The fluorine-carbon ratio of carbon fluoride is 1.2, and the chemical formula is CF 1.2 , the sheet diameter is 20 microns. After grinding the active material and conductive additives thoroughly, add sodium alginate, mix them evenly at high speed in the mixer, and then evenly apply the slurry on the aluminum foil. After it is completely dried, use the slicing mechanism to obtain the negative electrode.
[0106] Electrolyte system: The electrolyte is a 20 mol / kg (mass molar concentration) lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) solution, and the solvent is water.
[0107] The aqueous battery device of this embodiment is assembled using an aluminum-plastic film as the shell, a glass fiber as the separator, and a positive electrode to negative electrode mass ratio of 2:1.
[0108] Example 4
[0109] This embodiment provides a LiMn2O4-Li4Ti5O 12 Aqueous battery device and method for extending cycle life, LiMn2O4-Li4Ti5O 12 The preparation process of the aqueous battery device specifically includes:
[0110] Preparation of positive electrode: The positive electrode active material is lithium manganese oxide LiMn2O4. Weigh the positive electrode active material LiMn2O4, the conductive additive acetylene black, and the sodium alginate binder according to the mass ratio of 8:1:1. After the active material and the conductive additive are fully ground, add the sodium alginate, mix them evenly at high speed in the mixer, and then evenly apply the slurry on the aluminum foil. After it is completely dried, use the slicing mechanism to obtain the positive electrode.
[0111] Preparation of negative electrode: Li4Ti5O is used as negative electrode material 12 , weigh the negative electrode active material Li4Ti5O according to the mass ratio of 80:0.5:9.5:10 12 , SEI film-forming additive carbon fluoride, conductive additive acetylene black, and sodium alginate binder. The fluorine-carbon ratio of carbon fluoride is 0.8, and the chemical formula is CF 0.8 , the sheet diameter is 10 microns. After grinding the active material and conductive additives thoroughly, add sodium alginate, mix them evenly at high speed in the mixer, and then evenly apply the slurry on the aluminum foil. After it is completely dried, use the slicing mechanism to obtain the negative electrode.
[0112] Electrolyte system: The electrolyte is a 20 mol / kg (mass molar concentration) lithium bis(trifluoromethanesulfonyl)imide LiTFSI solution, and the solvent is water.
[0113] The aqueous battery device of this embodiment is assembled using an aluminum-plastic film as the shell, a glass fiber as the separator, and a positive electrode to negative electrode mass ratio of 2:1.
[0114] Example 5
[0115] This embodiment provides a NaMnHCF-NaV6O 15 Aqueous battery device and method for extending cycle life, NaMnHCF-NaV6O 15 The preparation process of the aqueous battery device specifically includes:
[0116] Preparation of positive electrode: NaMnHCF is used as the positive electrode active material. The positive electrode active material NaMnHCF, the conductive additive Super P, and polytetrafluoroethylene (PTFE) are weighed in a mass ratio of 8:1:1, wherein PTFE exists in the form of being dissolved in N-methylpyrrolidone (NMP) solution. The active material, the conductive additive, and PTFE are fully ground together, and then pressed into a pole piece by a dry pressing method.
[0117] Preparation of negative electrode: NaV6O is used as negative electrode material 15 , weigh the negative electrode active material NaV6O according to the mass ratio of 80:3:7:10 15 , fluorinated graphene as a SEI film-forming additive, Super P as a conductive additive, and polytetrafluoroethylene (PTFE), where PTFE exists in the form of being dissolved in NMP solution. The fluorine-carbon ratio of fluorinated graphene is 0.6, and its chemical formula is CF 0.6 The active material, conductive additive and PTFE are ground together and then pressed into pole pieces by dry pressing.
[0118] Electrolyte system: The electrolyte is a mixed solution of 9 mol / kg (mass molar concentration) sodium trifluoromethanesulfonate (NaOTF) solution and 22 m tetraethylammonium trifluoromethanesulfonate (TEAOTF) solution, and the solvent is water.
[0119] The aqueous battery device of this embodiment is assembled using an aluminum-plastic film as the shell, a PP diaphragm, and a positive electrode and a negative electrode mass ratio of 2:1.
[0120] Example 6
[0121] This embodiment provides a NaCuHCF-NaTi2(PO4)3 aqueous battery device and a method for extending the cycle life. The preparation process of the NaCuHCF-NaTi2(PO4)3 aqueous battery device specifically includes:
[0122] Preparation of positive electrode: NaCuHCF is used as the positive electrode active material. Weigh the positive electrode active material NaCuHCF, the conductive additive graphene, and the acrylamide-acrylate copolymer according to the mass ratio of 8:1:1, wherein the acrylamide-acrylate copolymer exists in the form of being dissolved in pure water. After the active material and the conductive additive are fully ground, the acrylamide-acrylate copolymer is added, and after high-speed uniform mixing in the mixer, the slurry is evenly coated on the aluminum foil. After being completely dried, the positive electrode is obtained using a slicing mechanism.
[0123] Preparation of negative electrode: NaTi2(PO4)3 is selected as the negative electrode material. The negative electrode active material NaTi2(PO4)3, SEI film-forming additive fluorinated carbon nanotubes, conductive additive graphene, and acrylamide-acrylate copolymer are weighed according to the mass ratio of 80:7:8:5. The acrylamide-acrylate copolymer exists in the form of being dissolved in pure water. The fluorine-carbon ratio of fluorinated carbon nanotubes is 0.7, and the chemical formula is CF 0.7 , the diameter of the sheet is about 8 microns. After grinding the active material and conductive additives thoroughly, add acrylamide-acrylate copolymer, mix them evenly at high speed in a mixer, and then evenly apply the slurry on aluminum foil. After it is completely dried, use a slicing mechanism to obtain the negative electrode.
[0124] Electrolyte system: The electrolyte is a mixed solution of 9 mol / kg (mass molar concentration) sodium bistrifluoromethanesulfonimide NaTFSI solution and 17 mol / kg sodium perchlorate NaClO4 solution, and the solvent is water.
[0125] The aqueous battery device of this embodiment is assembled using an aluminum-plastic film as the shell, a PP diaphragm, and a positive electrode and a negative electrode mass ratio of 2:1.
[0126] Example 7
[0127] This embodiment provides a NaCuHCF-V2O5 aqueous battery device and a method for extending the cycle life. The preparation process of the NaCuHCF-V2O5 aqueous battery device specifically includes:
[0128] Preparation of positive electrode: NaCuHCF is used as the positive electrode active material. Weigh the positive electrode active material NaCuHCF, the conductive additive graphene, and the acrylamide-acrylate copolymer according to the mass ratio of 8:1:1, wherein the acrylamide-acrylate copolymer exists in the form of being dissolved in pure water. After the active material and the conductive additive are fully ground, the acrylamide-acrylate copolymer is added, and after high-speed uniform mixing in the mixer, the slurry is evenly coated on the aluminum foil. After being completely dried, the positive electrode is obtained using a slicing mechanism.
[0129] Preparation of negative electrode: V2O5 is selected as the negative electrode material. The negative electrode active material V2O5, SEI film-forming additive fluorinated carbon nanotubes, conductive additive graphene, and acrylamide-acrylate copolymer are weighed according to the mass ratio of 80:7:3:10. The acrylamide-acrylate copolymer exists in the form of dissolving in pure water. The fluorine-carbon ratio of fluorinated carbon nanotubes is 1.0, the chemical formula is CF, and the sheet diameter is about 5 microns. After the active material and conductive additive are fully ground, add acrylamide-acrylate copolymer, mix them evenly at high speed in the mixer, and then evenly apply the slurry on the aluminum foil. After it is completely dried, use the slicing mechanism to obtain the negative electrode.
[0130] Electrolyte system: The electrolyte is a mixed solution of 9 mol / kg (mass molar concentration) sodium bistrifluoromethanesulfonimide NaTFSI solution and 17 mol / kg sodium perchlorate NaClO4 solution, and the solvent is water.
[0131] The aqueous battery device of this embodiment is assembled using an aluminum-plastic film as the shell, a PP diaphragm, and a positive electrode and a negative electrode mass ratio of 2:1.
[0132] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A water-based battery negative electrode SEI film-forming additive for inhibiting hydrogen evolution solid electrolyte interface, characterized in that: The chemical formula of the SEI film-forming additive is CF x , x is 0.6-1.2; The CF x Specifically including: a mixture of one or more of fluorinated graphite, fluorinated carbon, fluorinated graphene or fluorinated carbon nanotubes; During the first week of charging of the aqueous battery, a reduction reaction occurs at the negative electrode of the aqueous battery, and the SEI film-forming additive CF x The metal fluoride is reduced to form a SEI layer on the negative electrode of the aqueous battery.
2. The SEI film-forming additive according to claim 1, characterized in that: The aqueous battery is an aqueous lithium ion battery or an aqueous sodium ion battery; The aqueous battery negative electrode undergoes a reduction reaction, and the SEI film-forming additive CF x The reaction process of reduction to form metal fluoride is: CF x (s)+xZ + (aq)+xe - →xZF(s)+C(s); where Z is Li or Na; e - Electrons are transmitted to the negative electrode through an external circuit to participate in the electrochemical reaction during the charging process of the aqueous battery.
3. The SEI film-forming additive according to claim 1, characterized in that: The SEI film-forming additive CF x The lateral dimension, i.e. the flake diameter, is less than 20 microns.
4. A negative electrode plate for an aqueous battery, characterized in that: The aqueous battery negative electrode plate includes the aqueous battery negative electrode SEI film-forming additive for inhibiting hydrogen evolution as described in any one of claims 1 to 3.
5. The negative electrode plate of the aqueous battery according to claim 4, characterized in that: The mass proportion of the aqueous battery negative electrode hydrogen evolution inhibition SEI film-forming additive in the aqueous battery negative electrode plate is 0.5%-8%.
6. A method for forming an SEI layer on an aqueous battery negative electrode sheet by using the aqueous battery negative electrode hydrogen evolution inhibiting SEI film-forming additive according to any one of claims 1 to 3, characterized in that: The method comprises: Preparation of CF containing SEI film-forming additives x The negative electrode sheet; x is 0.6-1.2; Assembling an aqueous battery using the negative electrode sheet; The aqueous battery is charged. During the first week of charging of the aqueous battery, a reduction reaction occurs at the negative electrode of the aqueous battery, and the SE I film-forming additive CF x The metal fluoride is reduced to form a SE I layer on the negative electrode of the aqueous battery; Wherein, the reaction process of the reduction is: CF x (s)+xZ + (aq)+xe - →xZF(s)+C(s); where Z is Li or Na; e - Electrons are transmitted to the negative electrode through an external circuit to participate in the electrochemical reaction during the charging process of the aqueous battery.
7. The method according to claim 6, characterized in that The preparation method contains SE I film-forming additive CF x The negative electrode sheet specifically includes: The negative electrode active material, SE I film-forming additive CF x , the conductive additive is uniformly mixed and ground, and then a binder is added, and the mixture is stirred and mixed to obtain a slurry; The negative electrode sheet is obtained by preparing the slurry by a coating method or a dry method.
8. The method according to claim 7, characterized in that The negative electrode active material includes: an aqueous lithium ion battery negative electrode active material or an aqueous sodium ion battery negative electrode active material; The conductive additive includes: a mixture of one or more of carbon black, graphene, acetylene black, Ketjen black, Super P, and carbon nanotubes; The binder comprises: a mixture of one or more of polyvinylidene fluoride PVDF, polytetrafluoroethylene PTFE, acrylamide-acrylate copolymer, and sodium alginate.
9. An aqueous lithium-ion battery, characterized in that: The aqueous lithium-ion battery comprises the aqueous battery negative electrode sheet as described in claims 4-5 above.
10. An aqueous sodium ion battery, characterized in that: The aqueous lithium-ion battery comprises the aqueous battery negative electrode sheet as described in claims 4-5 above.
Citation Information
Patent Citations
Sodium-perfluorocarbon primary battery
CN103700858A
Electrode with fluorinated graphene as conductive agent and application in lithium ion batteries
CN104993145A
Method for preparing negative pole material from graphite fluoride and carbon nano-tubes for lithium-ion batteries
CN106395741A
Fluorinated graphene modified titanium dioxide material as well as preparation and application thereof
CN111244406A
Novel graphite fluoride composite lithium ion battery negative electrode material and preparation method thereof
CN111628168A